Burden of HIV-Related Stigma and Post-Partum Depression: A Cross-Sectional Study of Patients Attending Prevention of Mother-to-Child Transmission Clinic at Kenyatta National Hospital in Nairobi - Yator, Obadia; Mathai, Muthoni; Albert, Tele; Kumar, Manasi (Frontiers in Psychiatry, 2021)
Background: This study focused on how various HIV-related stigma subtypes interact with postpartum depression (PPD) among women living with HIV and ascertain key psychosocial risk factors that influence stigma and PPD among women attending Prevention of Mother-to-Child Transmission (PMTCT) clinic. Methods: This is a cross-sectional-mixed method design study involving123 women infected with HIV. Participants ages 18¬–50, who were at least eight weeks postpartum seeking PMTCT at Kenyatta National Hospital (KNH) between June and September 2014 services participated in the study. HIV/AIDS Stigma Instrument—PLWHA (HASI–P) was used to assesses stigma and Postpartum depression was assessed by Edinburgh Postnatal Depression Scale (EPDS). Bivariate and multivariate regression models were used to determine the individual characteristics associated with the HIV-related stigma Scale. In-depth-interviews was also conducted among some participants to explore on their perceptions and experiences while living with HIV. Results: The mean age was 31.2 years (SD=5.2). Fifty-nine (48%) women screened positive for significant depressive symptoms. Post-partum depression was a depression was a significant predictor of felt stigma, enacted and total stigma (P<0.05). Older age was associated with less felt stigma. Living with a partner was associated with more felt stigma. Having an income above 100 USD per month were protective against stigma. Having a good family social support was protective against felt stigma. Higher educational level was protective against enacted stigma. Being treated for STIs was a risk factor for both enacted and total stigma. Conclusions: HIV-related stigma needs to be addressed through integrated depression care program in PMTCT. Postpartum depression needs a comprehensive management to improve outcomes of women living with HIV.